Quality of the Live Birth Information System in the state of Paraná, from 2000 to 2005 - Silva, Gisele Ferreira da; Aidar, Tirza; Mathias, Thais Aidar de Freitas (Revista da Escola de Enfermagem da USP, 2011)
This study analyzed the quality of the Live Birth Information System in the State of (SINAC) Paraná, Brazil, from 2000 to 2005, through the percentage of undeclared variables, using a database provided by the State Health Department. Quality was analyzed using the following scale: excellent, undeclared percentage < 1%; good between 1% and 2.99%; regular between 3% and 6.99%; and poor > 7%. The quality in completing the SINAC in Paraná was excellent, especially as of year 2003. The mothers' occupation, classified as regular and poor, was the variable with the lowest quality in all Regional Health Departments. Live births, stillbirths, and race/color varied between poor and excellent quality. There is a need to improve the quality of the variables marital status and stillbirths in all Regional Health Departments. The excellence of the SINAC demonstrated its potential as a source of health information in Paraná.